The Effect Of Good Corporate Governance On Earnings Management Actions With Audit Tenure As A Moderating Variable - Irmasari; Sutrisno, Sutrisno; Roekhuddin, Roekhuddin (Institut Teknologi dan Bisnis Asia Malang, 2025)
This study aims to examine how Good Corporate Governance (GCG) constrains earnings management in companies, considering the tenure of the Public Accounting Firm (PAF) with the company. The population used in this research consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period from 2018 to 2022. The sampling technique employed is purposive sampling, resulting in a sample of 109 companies with 545 observations. The analysis technique used is multiple linear regression analysis. The testing used in this research is SPSS. The results of this study indicate that Good Corporate Governance can constrain earnings management. An independent board of commissioners and managerial ownership can minimize the occurrence of earnings management. However, the audit committee and institutional ownership cannot constrain the occurrence of earnings management. Audit tenure can weaken the influence of the independent board of commissioners in constraining earnings management. Audit tenure can strengthen the influence of institutional ownership in limiting earnings management. However, audit tenure does not moderate the influence of the audit committee and managerial ownership on the occurrence of earnings management.